Mutation - Cook, Robin (New York Pan Books, 1989)
When biomolecular researcher, Dr Victor Stein, applies his knowledge to create an ideal son, the child is born physically perfect and highly intelligent. But at the age of four, things start to go drastically wrong and terror ensues.
Keywords: Genetic engineering -- Massachusetts--Lawrence -- Horror tales